Residency and Space Use of Endangered Smoothhound Sharks ( Mustelus mustelus ) in Relation to Marine Protection and Demersal Longline Fishing Along South Africa's South Coast - Eugin Bornman; Taryn S. Murray; Neil Hammerschlag; Enrico Gennari (Fisheries Management and Ecology, 2026)
Shark populations are declining globally and the effectiveness of marine protected areas (MPAs) as a conservation tool may vary by species and environmental context. This study assessed space use and residency of smoothhound sharks ( Mustelus mustelus )—an endangered, yet highly exploited shark—in relation to spatial protection and fishing risk across three areas off the southern coast of South Africa. Passive acoustic telemetry data (2016–2023) from 37 individual sharks were analysed using residency indices and generalised additive models. Smoothhounds exhibited high site fidelity, with small daily home ranges ( 2 ). Residency showed a weak but significant negative relationship with fishing risk, indicating reduced residency in areas of higher fishing pressure. Residency was consistently higher within a MPA and adjacent bay waters, as compared to a nearby unprotected bay. These findings suggest that smoothhounds may respond to spatial protection and suggest that extending protection to the MPA‐adjacent high‐use areas could enhance conservation outcomes.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Fish Faunas from the Bissekty Formation (Turonian), Uzbekistan: Insights into biogeographic connectivity and climate-driven Faunal Turnover - Donald B. Brinkman; Martin Kundrát; David J. Ward; Alison M. Murray; Izzet K. Aimbetov; Lisa L. Van Loon; Neil R. Banerjee (Cretaceous Research, 2026)

Continuous nitrite and nitrate monitoring of recirculating aquaculture systems using a deployable ion chromatography-based analyser - Meritxell Grau Butinyac; Valeria Arenas Montaño; Jamie Downes; Neil M. Ruane; Elizabeth Ryder; Fintan Egan; Thomas Staessen; Brett Paull; Eoin Murray (Aquaculture International, 2024)

The radiometric environment for Mars limb observations by the Mars Sample Return Earth Return Orbiter - Marek Slipski; Armin Kleinböhl; Daniela Tirsch; Gerhard Kminek; Gregory Jonniaux; Klaus-Dieter Matz; Anni Määttänen; Austin Nicholas; Franck Montmessin; Soren N. Madsen; Matthew Abrahamson; Manuel Sanchez-Gestido; et al. (Advances in Space Research, 2023)

Corrigendum to “A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa” [Biol. Conserv. 284 (2023) 110163] - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

Acoustic tracking of a threatened juvenile shark species, the smooth hammerhead (Sphyrna zygaena), reveals vulnerability to exploitation at the boundary of a marine reserve - Patricia S. Albano; Chris Fallows; Monique Fallows; Lacey H. Williams; Taryn Murray; Oliver Sedgwick; Neil Hammerschlag (Frontiers in Marine Science, 2023)
The coastal waters of South Africa are habitat to a diverse composition of sharks that are vulnerable to exploitation, many of which are endemic and/or classified by the International Union for Conservation of Nature (IUCN) Red List as Threatened or Data Deficient. Accordingly, this region has been identified as a global research and conservation priority for elasmobranchs. The De Hoop Marine Protected Area (MPA), in the Western Cape Province of South Africa, provides 288 km 2 of no-take protection within its boundaries. However, the region experiences heavy commercial fishing, with two vessels actively operating as dedicated shark longliners (as of 2022). When crossing MPA boundaries, sharks are susceptible to capture by these vessels. Utilizing passive acoustic telemetry, the present study evaluated the movements of a threatened juvenile shark species, the smooth hammerhead ( Sphyrna zygaena ), both inside and adjacent to the De Hoop MPA, and along the greater coastline. Movement data from 20 tagged sharks were used to explore the effects of spatial, environmental, and management variables on their residency and movement patterns. Results indicate a high reliance of sharks on unprotected waters immediately adjacent to the MPA’s eastern boundary, an area of high biological productivity due to its proximity to the mouth of an estuary. Although some tagged sharks did move regionally along the South African coastline, individuals spent 95% of their days detected just outside the eastern boundary of the MPA, rendering them vulnerable to commercial shark longlining occurring there. These findings have conservation implications for smooth hammerhead sharks in South Africa and present an opportunity to revisit management practices that may optimize spatial protection for an important life stage of this threatened species.

Mapping mangrove alliances using historical data in Fiji - Brent A. Murray; Neil Sims; Joni Storie (Journal of Coastal Conservation, 2022)

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

Pulsed light reduces the toxicity of the algal toxin okadaic acid to freshwater crustacean Daphnia pulex - Iain M. T. Murray; Neil J. Rowan; Sara McNamee; Katrina Campbell; Andrew M. Fogarty (Environmental Science and Pollution Research, 2018)

Scope for genetic rescue of an endangered subspecies though re‐establishing natural gene flow with another subspecies - Katherine A. Harrisson; Alexandra Pavlova; Anders Gonçalves da Silva; Rebecca Rose; James K. Bull; Melanie L. Lancaster; Neil Murray; Bruce Quin; Peter Menkhorst; Michael J. L. Magrath; Paul Sunnucks (Molecular Ecology, 2016)
Genetic diversity is positively linked to the viability and evolutionary potential of species but is often compromised in threatened taxa. Genetic rescue by gene flow from a more diverse or differentiated source population of the same species can be an effective strategy for alleviating inbreeding depression and boosting evolutionary potential. The helmeted honeyeater Lichenostomus melanops cassidix is a critically endangered subspecies of the common yellow‐tufted honeyeater. Cassidix has declined to a single wild population of ~130 birds, despite being subject to intensive population management over recent decades. We assessed changes in microsatellite diversity in cassidix over the last four decades and used population viability analysis to explore whether genetic rescue through hybridization with the neighbouring Lichenostomus melanops gippslandicus subspecies constitutes a viable conservation strategy. The contemporary cassidix population is characterized by low genetic diversity and effective population size ( N e gippslandicus to cassidix has declined substantially relative to pre‐1990 levels and argue that natural levels of gene flow between the two subspecies should be restored. Allowing gene flow (~4 migrants per generation) from gippslandicus into cassidix (i.e. genetic rescue), in combination with continued annual release of captive‐bred cassidix (i.e. demographic rescue) , should lead to positive demographic and genetic outcomes. Although we consider the risk of outbreeding depression to be low, we recommend that genetic rescue be managed within the context of the captive breeding programme, with monitoring of outcomes.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Plant Diversity Hotspots in the Atlantic Coastal Forests of Brazil - CHARLOTTE MURRAY‐SMITH; NEIL A. BRUMMITT; ARY T. OLIVEIRA‐FILHO; STEVEN BACHMAN; JUSTIN MOAT; EIMEAR M. NIC LUGHADHA; EVE J. LUCAS (Conservation Biology, 2009)
Plant‐diversity hotspots on a global scale are well established, but smaller local hotspots within these must be identified for effective conservation of plants at the global and local scales. We used the distributions of endemic and endemic‐threatened species of Myrtaceae to indicate areas of plant diversity and conservation importance within the Atlantic coastal forests ( Mata Atlântica ) of Brazil. We applied 3 simple, inexpensive geographic information system (GIS) techniques to a herbarium specimen database: predictive species‐distribution modeling (Maxent); complementarity analysis (DIVA‐GIS); and mapping of herbarium specimen collection locations. We also considered collecting intensity, which is an inherent limitation of use of natural history records for biodiversity studies. Two separate areas of endemism were evident: the Serra do Mar mountain range from Paraná to Rio de Janeiro and the coastal forests of northern Espírito Santo and southern Bahia. We identified 12 areas of approximately 35 km 2 each as priority areas for conservation. These areas had the highest species richness and were highly threatened by urban and agricultural expansion. Observed species occurrences, species occurrences predicted from the model, and results of our complementarity analysis were congruent in identifying those areas with the most endemic species. These areas were then prioritized for conservation importance by comparing ecological data for each.

Phylogeography of the New Zealand blue duck (Hymenolaimus malacorhynchos): implications for translocation and species recovery - Bruce C. Robertson; Tammy E. Steeves; Katherine P. McBride; Sharyn J. Goldstien; Murray Williams; Neil J. Gemmell (Conservation Genetics, 2007)

The identification of chromosome abnormalities associated with the invasive phenotype of uveal melanoma in vitro - Neil A. Cross; Ian G. Rennie; Anna K. Murray; Karen Sisley (Clinical & Experimental Metastasis, 2005)

Gene flow on the ice: genetic differentiation among Adélie penguin colonies around Antarctica - Amy D. Roeder; Richelle K. Marshall; Amanda J. Mitchelson; Thungar Visagathilagar; Peter A. Ritchie; Donald R. Love; Trevor J. Pakai; Helen C. McPartlan; Neil D. Murray; Nick A. Robinson; Knowles R. Kerry; David M. Lambert (Molecular Ecology, 2001)
Each summer Adélie penguins breed in large disjunct colonies on ice‐free areas around the Antarctic continent. Comprising > 10 million birds, this species represents a dominant feature of the Antarctic ecosystem. The patchy distribution within a large geographical range, natal philopatry and a probable history of refugia, suggest that this species is likely to exhibit significant genetic differentiation within and among colonies. We present data from seven microsatellite DNA loci for 442 individuals from 13 locations around the Antarctic continent. With the exception of one locus, there was no significant genic or genotypic heterogeneity across populations. Pairwise F ST values were low with no value > 0.02. When all colonies were compared in a single analysis, the overall F ST value was 0.0007. Moreover, assignment tests were relatively ineffective at correctly placing individuals into their respective collection sites. These data reveal a lack of genetic differentiation between Adélie penguin colonies around the Antarctic continent, despite substantial levels of genetic variation. We consider this homogeneity in terms of the dispersal of individuals among colonies and the size of breeding groups and discuss our results in terms of the glacial history of Antarctica.

Tolerance to Thiarubrines from Ambrosia chamissonis by the Rare Moth Lasionycta wyatti - Joanna Dojillo-Mooney; Jonathan E. Page; Murray B. Isman; G. H. Neil Towers (Journal of Chemical Ecology, 1999)

Perceptual contributions to optimization of breathing - Yoshitaka Oku; Gerald M. Saidel; Murray D. Altose; Neil S. Cherniack (Annals of Biomedical Engineering, 1993)

Sensation and control of breathing: A dynamic model - Yoshitaka Oku; Gerald M. Saidel; Tatsuya Chonan; Murray D. Altose; Neil S. Cherniack (Annals of Biomedical Engineering, 1991)